Interactive effects of subjective memory complaints and hypertension on learning and memory performance in the elderly. Issue 2 (3rd March 2016) - Nguyen, Lauren A.; Haws, Kari A.; Fitzhugh, Megan C.; Torre, Gabrielle A.; Hishaw, Georg A.; Alexander, Gene E.
Abstract: This study evaluated whether the relation between subjective memory complaints and cognitive performance is influenced by the presence of hypertension in the elderly. One hundred and five healthy older adults, 70–89 years of age, with and without hypertension treatment or diagnosis, completed a scale of subjective memory complaints. Participants were divided into those with mild memory concerns and those with minimal or no complaints. All participants completed a battery of neuropsychological tests including measures of verbal and nonverbal memory. After controlling for differences in age, gender, education, and overall intellectual ability, there were significant main effects for memory concerns and significant interactions for memory complaints and hypertension on several measures of memory performance. There were no main effects for hypertension on memory performance. Simple effects analyses of the interactions showed that the hypertensive complainers demonstrated poorer performance on measures of long-term memory and greater reliance on short-term recall than the hypertensive non-complainers. There were no differences in memory performance for the non-hypertensive groups. Among healthy elderly community-dwelling adults, those with mild subjective memory complaints in the context of hypertension demonstrated greater objective cognitive difficulties than those without hypertension as well as a greater reliance on a less efficient learning strategy. These findings suggest that memory concerns in the presence of hypertension may be important when evaluating treatment efficacy in these individuals and for identifying differences in cognitive aging.